(untitled) (Global Journals of Research in Engineering, 2024)
The low thermal stability of cellulose presents unique technological challenges to the formulation of wood and plastic composites that are compatible and processable For this hydrothermal modification is a well-established technology for improving dimensional stability and durability of wood s components in addition to providing better interaction with the polymer This study produced polymer composites in which hydrothermally treated wood waste fibers WT reinforce a recycled polypropylene RPP matrix Wood waste fibers were selected by grain size and distribution treated hydrothermally and characterized by SEM ATR-FTIR and water sorption Composites were produced varying the reaction time of treatment hydrothermal from 30 to 180 minutes granulometric size from 425 to 1400 m and percentage of WT from 10 to 20 following a 2 full-factorial experimental design by extrusion with internal recirculation and the mechanical test specimens were modulated by injection Tensile flexion IZOD impact and water sorption tests were statistically analyzed Reaction time was the most statistically significant factor Composites of wood waste fibers treated for 30 min and containing 20 of WT presented better mechanical properties than expected However the preservation of the lamellar fibers during the reaction time allowed for better adherence to the polymer and the insertion of a greater quantity of fibers in the material provided greater rigidity in the composite In general the results obtained gives properties of stability and resistance to damage of composites containing hydrothermally treated wood fibers